Mulheres, retórica e anúncio publicitário: um olhar sobre o feminino na revista O Cruzeiro - Quintas, Claudia Mastromauro Cerveira (2018)
This thesis aims to establish the rhetorical strategies used and the way the feminine ethos is constituted in the advertisements placed in the Brazilian magazine O Cruzeiro from the 1920s to the 1970s. That weekly publication was one of the most powerful media in Brazil. For almost half a century, it set fashions, produced and promoted behavior norms and paved the paths for feminine transformation and upward social mobility in a period during which Brazil sought for the urbanization of its big metropoles and pursued an authentically Brazilian cultural history. As a means to guarantee satisfactory analysis, the studies of Aristotle (2003, 2004, 2007, 2009), Chaïm Perelman and Lucie Olbrechts-Tyteca (2005), Michel Meyer (2007) and Olivier Reboul (2004) underpin the exposed historical and theoretical considerations on Classic Rhetoric and New Rhetoric. When it comes to the principles of rhetorical analysis, the studies by Luiz Antonio Ferreira (2010), were also used. We found most of the support for publicity text analyses in the works by Marília Scalzo (2013), Antônio Sandmann (2003), Nelly de Carvalho (2002) and João Anzanello Carrascoza (1999). In order to discuss the magazines, our work was based on the works by Roberto Civita (2000), Fernando Morais (2001), Accioly Netto (1998) and Leoni Teresinha Vieira Serpa (2003), and finally, regarding the approach to the feminine universe, we made use of the reflexions by Mary Del Priori (2011) and Michelle Perrot (2013). It is relevant to highlight that other rhetoric, advertising, magazine and feminine universe scholars have also contributed to the development of this research. At the wrapping up of this investigation, we concluded that the selected publicity pieces spotlight the presence of persuasive rhetorical strategies, as well as an effective constitution of the feminine ethos. We have verified the occurence of rhetorical figures and places and the ubiquity of the epideitic/laudatory genre in the discourse analysed, which promotes closeness between the speaker and the audience